The way of the strangers : encounters with the Islamic State - Wood, Graeme (Journalist) (New York : Random House, 2017)
The Way of the Strangers is an intimate journey into the minds of the Islamic State's true believers. From the streets of Cairo to the mosques of London, Wood interviews supporters, recruiters, and sympathizers of the group. Wood speaks with non-Islamic State Muslim scholars and jihadists, and explores the group's idiosyncratic, coherent approach to Islam. Through character study and analysis, Wood provides a clear-eyed look at a movement that has inspired so many people to abandon or uproot their families.
The Islamic State view of humanity -- A note on terminology -- Prologue -- The chosen sect -- Madness and methodology -- Musa cerantonio -- Yahya the American -- A dream deferred -- Dissent -- The war of the end of time -- Afterlife.
Includes bibliographical references (pages 285-305) and index.
Keywords: IS (Organization); Terrorists -- Iraq; Terrorists -- Syria; Terrorism -- Religious aspects -- Islam; Middle East -- History -- 21st century; Middle East; Syria; History